2019
DOI: 10.1097/yco.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the gut–brain axis in schizophrenia and bipolar disorder

Abstract: Purpose of review Schizophrenia (SCZ) and bipolar disorder are severe mental disorders, both placing a significant burden on individuals' wellbeing and global health generally. The complex interaction of multiple mechanisms, underlying these disorders, still needs further elucidation. Increased activation of components of the immune system may be involved, including alterations in intestinal permeability and gut microbiome. Probiotics, defined as living microorganisms conferring health benefits to the host whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…We have previously reported that changes in the gut microbiota of pregnant mice result in changes in the gut microbiota of the offspring and increases of anxious behavior [ 11 ]. Alterations of gut microbiota in several mental disorders, such as autism spectrum disorder (ASD), schizophrenia, and depression, have also been reported [ 12 , 13 , 14 ]. In particular, patients with ASD and schizophrenia show impairment of social behaviors as a symptom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that changes in the gut microbiota of pregnant mice result in changes in the gut microbiota of the offspring and increases of anxious behavior [ 11 ]. Alterations of gut microbiota in several mental disorders, such as autism spectrum disorder (ASD), schizophrenia, and depression, have also been reported [ 12 , 13 , 14 ]. In particular, patients with ASD and schizophrenia show impairment of social behaviors as a symptom.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients with ASD and schizophrenia show impairment of social behaviors as a symptom. The alterations of many bacterial abundances such as Bifidobacterium, Lactobacillus, Bacteroides, Ruminococcaceae, or Verrucomicrobia have been reported in patients with ASD or schizophrenia [ 12 , 14 , 15 , 16 ], which suggests the possibility that the gut–brain axis may affect social behavior. In addition, stress reportedly affects gut microbiota [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further benefit of the KD is its ability to alter the gut microbiome, which in the context of the evolving understanding of the gut-brain axis in psychiatric research ( 44–46 ) could prove particularly meaningful. In terms of overall balance of gut microbiota, there are a series of studies covering a range of age groups that demonstrate the KD’s positive impact on dysbiosis ( 47–49 ).…”
Section: Achieving Ketosismentioning
confidence: 99%
“…Clinical trials have demonstrated the efficacy of probiotic supplementation in ameliorating mental illness. The clinical efficacy of probiotics coupled with their lack of detrimental side effects and stigmatization make them a promising therapeutic intervention in mental disorders [26][27][28][29]. Although existing clinical trials are limited and more substantial research outcomes are needed, probiotics are a noteworthy therapeutic intervention as far as the mental health domain is concerned.…”
Section: Introductionmentioning
confidence: 99%